Analisis Kalor Bioetanol Berbahan Dasar Sabut Kelapa - Nadliroh, Kuni; fauzi, Ah. Sulhan; Maulidina, Miftakhul (Jurnal Mesin Nusantara, 2022)
Bioethanol is an alternative fuel that can be used as a substitute for fuel. Bioethanol can be produced from the fermentation of sugar from carbohydrates or sugar. The content of bioethanol that can be used as fuel has a minimum alcohol content of 10%. This research is a follow-up study from previous research regarding the manufacture of bioethanol made from young coconut ice seller waste, namely coconut fiber. Where the result of the result of the research is that the resulting bioethanol contains quite a lot of alkohol. The waste of young coconut ice sellers can produce bioethanol produced from the fermentation process. The aims of this research determine the calorific value of bioethanol from reflux distillation from coconut fiber. The methode is used a calorimeter bomb. Test were carried out on bioethanol derived from young coconut ice waste, namely coconut shell. The research was conducted on bioethanol from coconut fiber by going through a reflux distillation process. The results showed that the highest calorific value was produced by type C samples with 28 days of fermentation, the calorific value was 3940 cal/gram.